A reproducible and versatile system for the dynamic expansion of human pluripotent stem cells in suspension. Issue 10 (11th August 2015) - Elanzew, Andreas; Sommer, Annika; Pusch‐Klein, Annette; Brüstle, Oliver; Haupt, Simone
Abstract Reprogramming of patient cells to human induced pluripotent stem cells (hiPSC) has facilitated in vitro disease modeling studies aiming at deciphering the molecular and cellular mechanisms that contribute to disease pathogenesis and progression. To fully exploit the potential of hiPSC for biomedical applications, technologies that enable the standardized generation and expansion of hiPSC from large numbers of donors are required. Paralleled automated processes for the expansion of hiPSC could provide an opportunity to maximize the generation of hiPSC collections from patient cohorts while minimizing hands‐on time and costs. In order to develop a simple method for the parallel expansion of human pluripotent stem cells (hPSC) we established a protocol for their cultivation as undifferentiated aggregates in a bench‐top bioreactor system (BioLevitator™). We show that long‐term expansion (10 passages) of hPSCs either in mTeSR or E8 medium preserved a normal karyotype, three‐germ‐layer differentiation potential and high expression of pluripotency‐associated markers. The system enables the expansion from low inoculation densities (0.3 × 105 cells/mL) and provides a simplified, cost‐efficient and time‐saving method for the provision of hiPSC at midi‐scale. Implementation of this protocol in cell production schemes has the potential to advance cell manufacturing in many areas of hiPSC‐based medical research.